[TM13@Bi20]− clusters in three-shell icosahedral matryoshka structure: being as superatoms. Issue 112 (27th October 2015) - Kou, C. Y.; Zhuang, L.; Wang, G. Q.; Cui, H.; Yuan, H. K.; Tian, C. L.; Wang, J. Z.; Chen, H.
Abstract : Using the density functional theory (DFT) method, three-shell icosahedral matryoshka [TM13 @Bi20 ] − clusters (TM = 3d, 4d) have been systematically examined to explore the possibility of clusters being as superatoms. Abstract : Using the density functional theory (DFT) method, the 33-atom intermetalloid [TM13 @Bi20 ] − clusters (TM = 3d, 4d), which are composed of Bi20 pentagonal dodecahedra surrounding TM12 icosahedra with a single TM atom at the center, have been systematically examined to explore the possibility of clusters being as superatoms. The results show that most TM13 clusters can be attractively encapsulated into Bi20 cage to form a stable core–shell configuration, exhibiting an interesting progression of thermal stability along the 3d and 4d periods. Taking into account the structural stability (binding energy, embedding energy, and core–shell interaction) as well as the chemical stability (HOMO–LUMO gap), we proposed that [TM13 @Bi20 ] − clusters with Ti and Mn doping in 3d series (Zr and Ag doping in 4d series) are specially stable and to be the protyle superatoms. For such systems, the molecular orbital shapes and energy alignments are in analogy with the atomic patterns, coinciding the general characters of superatomic orbitals. The closed core superatomic shell together with the partially-filled valence superatomic shell configuration leads to magnetic moment in stable [TM13 @Bi20 ] −, e.g., [Mn13 @Bi20 ] − cluster with the half-filled subshell can be assigned as a magnetic superatom owning to its modest HOMO–LUMO gap of 0.37 eV and large magnetic moment of 36 μ B . The exchange-splitting in TM-3d states is found to be the driving force for the improvement of exchange-splitting of superatomic states.